PENERAPAN MEDIA PEMBELAJARAN DARING DENGAN MEMANFAATKAN APLIKASI DISCORD PADA MATA PELAJARAN IPA TERPADU SELAMA PANDEMI COVID-19 DI KELAS VIII-2 SMP NEGERI 2 TEBING TINGGI - Floria Panggabean (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to analyze the potential of one of the social media applications, Discord, to be used in online learning during the Covid-19 period  and describe the improvement of student learning outcomes of science subject in class VIII-2 SMP Negeri 2 Tebing Tinggi. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class VIII-2 SMP Negeri 2 Tebing Tinggi which is amounted to 36 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the discord media application of science subjects can improve student learning result which is characterized by increased mastery learning students, namely pre-cycle (58,3%), the first cycle (75%), cycle II (86,1 %) and complete learn the clasical equal to 86,1 %. Key word :online, discord, science